Identifikasi Preferensi Pengunjung Terhadap Ruang Pada Warung Begos Dalam Studi Pemetaan Perilaku - Iftitah, Ummul; Ibrahim Rahmani, Ahmad (TIMPALAJA : Architecture Student Journals, 2022)
Relations between humans and the environment in the public sphere tend to be an environmental determinant. A relationship where environmental factors are more influential in the formation of human behavior than internal factors within him. This kind of relationship also applies in public spaces such as fast food restaurants which are now commonly found in everyday life. This study identified that the spatial aspects that influence visitor preferences in behaving in space are the type and placement of furniture and wall-forming elements. at the same time, another aspect that also affects the mapping of visitor behavior is the density or density of visitors which varies depending on the time of visit. This study describes the behavioral patterns of visitors and the interior elements that influence this behavior at a Begos fast-food restaurant located in a culinary center in Gowa. The method used is a place-centered map method based on a behavioral approach.